Management of Hickory Forest Understory Vegetation Increases Ecosystem Carbon Sequestration, But It Also Increases Soil Greenhouse Gas Emissions in the Short Term - Haitao Shi; Yangen Chen; Sha Huang; Xuekun Cheng; Huiying Chen; Ruizhi Xu; Yufeng Zhou; Yongjun Shi (Agronomy)
Managing forest understory has a significant impact on soil greenhouse gas (GHG) emissions and the ecosystem’s capacity for carbon sequestration. However, its specific impacts and mechanisms within hickory (Carya cathayensis Sarg) forests remain unclear. The objective of this study was to examine the effects of different understory vegetation treatments on hickory stands with similar growth history, site conditions, and slopes: Cinnamomum chekiangense (Cinnamomum chekiangense Nakai) and strip-sown ryegrass (Lolium perenne L.) (CR1), Cinnamomum chekiangense and scattered ryegrass (CR2), Torreya grandis (Torreya grandis’ ‘Merrillii’ Hu) and strip-sown wild rapeseed (Brassica napus L.) (TW1), Torreya grandis and scattered wild rapeseed (TW2), and removal of understory vegetation (CK). Twenty experimental plots were established at the Lin’an Forestry Carbon Sink Pioneer Base, and after 12 months of monitoring, the responses of GHG emissions, vegetation, and soil organic carbon (SOC) sequestration were analyzed, revealing the differences in ecosystem carbon sequestration capacity. Compared to CK, CR1, CR2, TW1, and TW2 increased the global warming potential (GWP) by approximately 26%, 55%, 26%, and 16%, respectively. The SOC increased by approximately 76%, 102%, 51%, and 32%, respectively, while the vegetation carbon sink increased by approximately 30%, 27%, 53%, and 62%, respectively. In summary, ecosystem carbon sequestration increased by approximately 109%, 98%, 95%, and 92%, respectively. The findings indicate that managing understory vegetation in pecan forests significantly enhances ecosystem carbon sequestration but also increases soil GHG emissions. To enhance future research priorities, it is essential to focus on increasing carbon sequestration in hickory forests and managing soil GHG emissions through effective and rational understory vegetation management.